Problematika Linguistik Dalam Penggunaan Bahasa Indonesia Pada Siswa/I Sekolah Indonesia Jeddah - Fahmi, Kaula; Saiddah, Ghina Widia; Khotami, Rizqi Shohibul; Al-Muqmin, Hawa Dita (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study examines the dynamics of Indonesian language usage at the Indonesian School in Jeddah (SIJ) within a multilingual environment in Saudi Arabia. A descriptive qualitative study using a case study design aims to explore students' linguistic problematics through participatory observation, interviews, and documentation. Research findings reveal a complex pattern of Indonesian language usage, characterized by code-mixing, code-switching, and interference from Arabic and English languages. Students face significant challenges, including grammatical errors, vocabulary limitations, and communicative obstacles. Geographical, social, psychological, and educational factors simultaneously influence students' language competence. This study highlights the importance of developing innovative and contextual Indonesian language teaching methods in international educational settings, with theoretical and practical implications in the field of sociolinguistics.